Simulations and Games in Teaching International Relations and Strategic Studies - da Silva, Igor Castellano; Lyra, Luiza K.; Paludo, Isabella G. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
International Relations (IR) and Strategic Studies (SS) have long utilized games and simulations as educational tools, especially in digital settings. Recently, these fields have evolved from technical training and executive action to interdisciplinary areas within the Social Sciences. This shift reflects a change in training objectives, moving from technical skills to a broader understanding of complex global dynamics. Modern approaches aim to foster a deep comprehension of these dynamics using diverse analytical lenses. This article examines the legacy of IR and SS in the contemporary use of gamification and simulations in education, highlighting their role in recent structural transformations. The research employs a hypothetical-deductive method, utilizing bibliographic techniques to explore the co-constitution of IR, SS, and educational gaming.